SISTEM DAN PROSEDUR PEMBELIAN BARANG DAGANG SERTA PENENTUAN HARGA POKOK PENJUALAN PADA PT PERHUTANI (PERSERO) - Fransiska Elisa; Fenny BNL Tobing; Nenny Anggraeny (Fakultas Ekonomi Universitas Kristen Indonesia, 2018)
Purchases can not be ruled out in the operational activities of a company for the purchase of an item that can be used in providing and resold to another party. System strong purchases of merchandise as well as the purchase of standardized procedure is crucial in the implementation of the purchase, that purchase activity can be accounted for properly. Many products produced by PT Perhutani (Persero) which one of them in the field of national beekeeping center or abbreviated Pusbahnas. Activities undertaken in Pusbahnas is processing local honey and honey purchased through partners through several methods such as open auctions, direct elections, direct appointment, direct procurement and self-management. In this case PT Perhutani especially those Pusbahnas choose the method of selecting an open and self-management were taken from areas in Central Java. in procuring raw material using the acceptance of the honey from the partners and in selling their products using cost of goods sold which then essentially determine the selling price. Systems and procedures for purchases of merchandise as well as determining the cost of sales is very important for the company to process the raw materials for use in both internal and sold to the public for consumption.Kata kunci: Pembelian, Sistem, Persediaan, Prosedur, Harga pokok penjualan.